PERBANDINGAN PMK NO 68/PMK.03/2022 PAJAK ASSET UANG KRIPTO DI INDONESIA DENGAN BERBAGAI NEGARA-NEGARA LAIN - Safri, Safri; Setiadi, Setiadi (JURNAL BISNIS & AKUNTANSI UNSURYA, 2022)
The Indonesian tax authority, in this case the Ministry of Finance, has issued PMK No. 68/PMK.03/2022, regarding value added tax and income tax on crypto asset trading transactionsComparing the value added tax on Indonesian Crypto Assets, only France stipulates VAT, but only applies if you pay for goods in Bitcoin and does not charge VAT on Bitcoin sales, while other countries have not set VAT.Comparison of Income Tax on crypto assets in Indonesia, the United States, China, Hong Kong, England, Japan, Germany, Norway, France, and Spain determines income tax in the form of capital gains, with different provisions, whereThere are several countries with crypto asset tax implementations that are different from Indonesia's regulations, these countries are, India applies a policy of all digital money assets being taxed, Kazakhstan applies a tax policy on crypto assets only for mining. And there are countries that can be called crypto asset tax havens including Belarus, the state of Georgia and Illinois, and Portugal.Â Keywords: Crypto Assets, Value Added Tax, income tax